If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + -4 = 10y + 3 + -9y Combine like terms: 4 + -4 = 0 0 = 10y + 3 + -9y Reorder the terms: 0 = 3 + 10y + -9y Combine like terms: 10y + -9y = 1y 0 = 3 + 1y Solving 0 = 3 + 1y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. 0 + -1y = 3 + 1y + -1y Remove the zero: -1y = 3 + 1y + -1y Combine like terms: 1y + -1y = 0 -1y = 3 + 0 -1y = 3 Divide each side by '-1'. y = -3 Simplifying y = -3
| 0.9x-1.9y=1.43 | | x+2y=1.5 | | 15+8x-3x^2=0 | | 14m+7n-2mn+n= | | -4+-2+x=180 | | 20z+1=24z+7 | | -7-5x+4=-24x+18-5x | | (2x+10)+(x-10)+(2x-20)=180 | | (9x+24)=(6+66) | | -4x^2=8x-3 | | (X+30)+(2x)+(3x-30)=180 | | 12x-11x-2=-4 | | 2x^3-6x^2+4x-12=0 | | 7(x+7)=30 | | 6y=3.5 | | (2x)+(x+10)+(3x-10)=180 | | -9+2=-16 | | 5(x+4)+5=1 | | -3x-1.5y=0 | | 8y-12=6+2(10y-3) | | 2/3=k/9 | | 4/3=24/r | | 4/3=23/r | | 4x^2+8=10 | | -2(x+2)-4(x-3)=22 | | X+86+35+63+x=180 | | (2x)+(x+10)+(3x-7)=180 | | 3x=3.84 | | -5t-4(2+2t)=-4 | | 4+5u=9 | | 2x(x+1)+9=(3x+1)(x-1) | | 6(2m-8)=36 |